2013
DOI: 10.12678/1089-313x.17.4.159
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in Irish Dance

Abstract: Irish dance is growing in popularity and competitiveness; however, very little research has focused specifically on this genre of dance. The purpose of this study was to analyze the types of dance injuries incurred by Irish dancers. A chart review was performed to identify all injuries associated with Irish dance seen in the sports medicine or orthopaedic clinics at the investigators' hospital over an 11-year period. "Injury" was defined as any dance-related pain or disorder that led to evaluation in the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…As in other dance genres however (Thomas & Tarr, ) the accompanying risk of musculo‐skeletal pain and injury in ID can be substantial. Studies have reported rates of injury ranging from 55.9% (Stein et al., ) in adolescent amateur Irish dancers to 76.6% (Cahalan & O'Sullivan, ) in adult professional Irish dancers. Previous cross‐sectional research has identified that a combination of biopsychosocial and individual factors were associated with pain and injury in elite adult Irish dancers (Cahalan et al., ).…”
mentioning
confidence: 99%
“…As in other dance genres however (Thomas & Tarr, ) the accompanying risk of musculo‐skeletal pain and injury in ID can be substantial. Studies have reported rates of injury ranging from 55.9% (Stein et al., ) in adolescent amateur Irish dancers to 76.6% (Cahalan & O'Sullivan, ) in adult professional Irish dancers. Previous cross‐sectional research has identified that a combination of biopsychosocial and individual factors were associated with pain and injury in elite adult Irish dancers (Cahalan et al., ).…”
mentioning
confidence: 99%
“…The role of an Irish dancer requires not only a high degree of muscular power and endurance but also movement aesthetics. 6 It is interesting that even though dancers in the study were fatigued, the maximal verticaljump height attained did not change from prefatigue to postfatigue. This result is contrary to previous findings that highlighted a reduction in vertical-jump height of teamsport athletes when fatigued, 21,22 potentially as a protective mechanism to reduce injury risk.…”
Section: Discussionmentioning
confidence: 81%
“…The right limb was chosen as the test limb because right-sided injury is more prevalent among this population due to the strong leading pattern of the right lower limb. 6 Adequate rest (45 seconds, allowing for a work-to-rest ratio of 1 : 9) 14 was provided between trials to minimize the effect of fatigue during the prefatigue landing trials.…”
Section: Landing Movementmentioning
confidence: 99%
See 2 more Smart Citations